Perbedaan Hasil Belajar Siswa Menggunakan Model Pbl Berbantuan Lkpd dengan Berbantuan Kahoot (Studi Kasus Pada Materi Alat Pembayaran Mata Pelajaran Ekonomi Di SMAN 4 Jember Semester Genap Tahun Ajaran 2023/2024) - Lestari, Suci Endah Dwi; Sukidin; Mardiana, Lisana Oktavisanti (Universitas Pendidikan Ganesha, 2025)
The ability of students to actively participate in the learning process, skilled in the use of technology, become literate people, and have noble character is the main focus of 21st century learning. 21st century learning changes the learning approach from teacher centered to student centered. The rapid development of technology and the change in the learning approach to student centered in the 21st century requires collaboration between learning and technology, this is supported by the lives of students who go hand in hand with technology in their daily lives. Regarding this, the teacher plays an important role in choosing the appropriate learning model. For this reason, an interesting learning tool is needed, one of which is the Problem Based Learning model assisted by kahoot. The purpose of this study was to compare student learning outcomes using the Problem Based Learning model assisted by LKPD with the Problem Based Learning model assisted by Kahoot. The type of research used is quasi experimental design using nonequivalent control group design. Sampling using purposive sampling. Data collection techniques are tests, interviews, documents, and tests. The data analysis technique used was independent sample t-test. The results showed that there was a significant effect of Problem Based Learning model assisted by Kahoot rather than Problem Based Learning model assisted by LKPD on learning outcomes with a significant value of 0.000. It is expected that schools can improve the quality of school facilities so that it can facilitate learning in the classroom by adding Wi-Fi near classes that are far from the Wi-Fi network center.